Organizing Manage of International Half Marathon "Run for Peace and Tolerance" - Arijana Lllagjevic-Govori; Enver Tahiraj; Dardan Llagjaj; Fatlum Grajqevci; Abdurrahman Shkodra (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
Now that sport is in step up with time and other technologies, and it is imposed also the attending of sport`s organizing, from the minor to the grand organizing and all of them bring benefits not only to federation but to the country too, in order of presentation of the best as it`s possible, so all this depends mainly by respecting some specific rules, tasks, structure and organizing to what this event is organized for. In this work we present a model of managing the organizing the half marathon activity which is organized for many years, which is known also in the international area. This work paper deals with organizing of this competition that is named as an international activity for many years. This work paper is dealt with organizing of this competition that already has a long experience and within itself we find the organizing forms and hierarchy from the top to the competitors that does its activity on track. This form of organizing is done in the line Kosovo Athletic Federation, Ministry of sports and sponsors that is support in continuity this international competition. In this international half-marathon participants were 900 athletes from over 40 countries, then in organizing is provided awards in money and according to the age and psych-physical abilities that are presented in chart.